TINGKAT KONTAMINASI ANGGREK Vanda limbata DENGAN EKSTRAK BAHAN ALAMI YANG BERBEDA SECARA IN VITRO - Yuni Astriani Dewi, Ni Putu; Yasintha Moi, Maria; Asti Funan, Magdalena (Jurnal Biogenerasi, 2024)
The aim of this research to determine the lowest percentage of contamination and growth of Vanda limbata orchids with the addition of organic media extract. This research was carried out from July to September 2022 at the Biology Education Laboratory, Faculty of Teacher Training and Education, University of Timor. This study used a randomized block design with 3 natural media treatments (tomato extract, bean sprouts and Ambon banana) with 5 replications. From this research, it can be shown that natural-based media with tomato extract showed the lowest percentage of contamination, namely 0%. With the addition of tomato extract, it was able to stimulate the growth of Protocorm Likes Bodies (PLB) at the age of 27 days after planting compared to organic media with the addition of bean sprout extract and media. organic with the addition of Ambon banana extract and the highest percentage of contamination was found in organic media with the addition of Ambon banana extract, namely 16%.